Harry Emerson Fosdick : preacher, pastor, prophet - Miller, Robert Moats (Oxford University Press, 1985)
A major figure in American religious and cultural history, Fosdick was famous as a preacher, a pacifist and a champion of civil rights. He was also the author of forty-seven books.